PENGARUH NILAI PELANGGAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN MENGINAP DI ALPHA HOTEL PEKANBARU - Sera Prasetya; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of customer value and corporate image on customer satisfaction Alpha Hotel Pekanbaru. Customer value as variable (X1) corporate image as variable (X2) and customer satisfaction as (Y).The method in this research is descriptive and quantitative by using SPSS program, where the sample used is guest who stay more than 2 times in Alpha Hotel Pekanbaru with 100 0rang respondents. To determine the amount of smpel used slovin formula, as well as sampling techniques by accidental sampling. Data collection techniques through questionnaires and interviews.The result of analysis use multiple linear regression, t test, and f test so that it can be seen that customer value variable have positive effect to customer satisfaction, that giving image of company has a significant effect to customer satisfaction, and significant influence between customer value and company image to customer satisfaction